A mesh-free approach for fracture modelling of gravity dams under earthquake - Das, R.; Cleary, P. W. (International journal of fracture, 2013)
Fracture is a major cause of failure for concrete gravity dams. This can result in the large-scale loss of human lives and enormous economic consequences. Numerical modelling can play a crucial role in understanding and predicting complex fracture processes, providing useful input to fracture-resistant designs. In this paper, the use of a mesh-free particle method called smoothed particle hydrodynamics (SPH) for modelling of gravity dam failure subject to fluctuating dynamic earthquake loads is explored. The structural response of the Koyna dam is analysed with the base of the dam being subjected to high-intensity periodic ground excitations. The SPH prediction of the crack initiation location and propagation pattern is found to be consistent with existing FEM predictions and experimental results from physical models. The transient stress field and the resulting damage evolution in the dam structure were monitored. The amplitude and frequency of the ground excitation is shown to have considerable influence on the fracture pattern and the associated energy dissipation. The fluctuations in the kinetic energy of the dam wall and its fragments are found to vary with different frequencies and amplitudes as the structure undergoes progressive fracture. The dynamic responses and the fracture patterns predicted establish the strong potential of SPH for fracture modelling of dams and similar large structures.